Synergistic Effect between Trichoderma virens and Bacillus velezensis on the Control of Tomato Bacterial Wilt Disease - You Zhou; Laying Yang; Jun Wang; Lijia Guo; Junsheng Huang (Horticulturae, 2021)
(1) Background: Ralstonia solanacearum causes tomato bacterial wilt disease, one of the most serious tomato diseases. As the combination of Trichoderma virens (Tvien6) and Bacillus velezensis (X5) was more effective at controlling tomato bacterial wilt disease than a single agent, we investigated the synergistic effect of Tvien6 and X5 in controlling this disease; (2) Methods: The disease incidence, plant heights and weights, relative chlorophyll content (SPAD values), defensive enzymes (PPO, POD, and SOD) activities, and metabolome were estimated among four treatment groups (BR treatment, X5 + R. solanacearum (RS-15); TR treatment, Tvien6+ RS-15; TBR treatment, Tvien6 + X5 + RS-15; and R treatment, RS-15); (3) Results: The R treatment group had the highest disease incidence and lowest plant heights, plant weights, SPAD values, defensive enzyme activities, and D-fructose and D-glucose contents; the TBR treatment group had the lowest disease incidence and highest plant heights, plant weights, SPAD values, defensive enzyme activities, and D-fructose and D-glucose contents; (4) Conclusions: The results revealed that Tvien6 and X5 can both individually promote tomato plant growth, increase leaf chlorophyll content, enhance defensive enzyme activities, and induce the accumulation of D-fructose and D-glucose; however, they were more effective when combined.